Magnetic Solid Phase Extraction Applied to Food Analysis - Israel S. Ibarra; Jose A. Rodriguez; Carlos A. Galán-Vidal; Alberto Cepeda; Jose M. Miranda (Journal of Chemistry)
Magnetic solid phase extraction has been used as pretreatment technique for the analysis of several compounds because of its advantages when it is compared with classic methods. This methodology is based on the use of magnetic solids as adsorbents for preconcentration of different analytes from complex matrices. Magnetic solid phase extraction minimizes the use of additional steps such as precipitation, centrifugation, and filtration which decreases the manipulation of the sample. In this review, we describe the main procedures used for synthesis, characterization, and application of this pretreatment technique which were applied in food analysis.